Alterations in cyst fluid genetics following endoscopic ultrasound-guided pancreatic cyst ablation with ethanol and paclitaxel - DeWitt, John M.; Al-Haddad, Mohamad; Sherman, Stuart; LeBlanc, Julia; Schmidt, Christian M.; Sandrasegaran, Kumar; Finkelstein, Sydney D. (Endoscopy, 2014)
Background and study aims: Endoscopic ultrasound (EUS)-guided ethanol lavage with paclitaxel injection has been shown to be effective for the treatment of pancreatic cystic neoplasms; however, the evidence for effectiveness is based primarily on cyst resolution on imaging. The aim of this study was to evaluate changes in pancreatic cyst fluid DNA following EUS-guided pancreatic cyst ablation (PCA) with ethanol and paclitaxel.Patients and methods: In a single-center, prospective study, patients with suspected benign pancreatic cysts (15 – 50 mm in diameter; ≤ 5 compartments) underwent EUS-PCA with ethanol and paclitaxel followed 3 months later by repeat EUS-FNA, cyst aspiration for repeat DNA analysis, and possible repeat EUS-PCA. Abdominal imaging was repeated 3 – 4 months and 12 months after the second EUS. Changes in baseline pancreatic cyst fluid DNA, procedural complications, and radiographic changes in cyst volume were evaluated.Results: A total of 22 patients (median age 67 years; 15 women) with cysts in the head or uncinate (n = 10), body or neck (n = 8), and tail (n = 4), measuring a median diameter of 25 mm (range 15 – 43 mm), underwent one (n = 22) or two (n = 9) EUS-PCA procedures. Baseline cyst DNA included mutations in 11 patients (50 %). Postablation cyst fluid (n = 19) showed elimination of all baseline mutations in eight patients, new mutations in three, and no changes in eight without a baseline mutation. The largest per-protocol postablation image-defined volume change (n = 20) from either of the follow-up abdominal imaging studies (n = 20) demonstrated complete response ( < 5 % original volume) in 10 patients (50 %), partial response (5 % – 25 % original volume) in 5 (25 %), and a persistent cyst (> 25 % original volume) in 5 (25 %). During a median follow-up of 27 months (range 17 – 42 months), adverse events from all EUS-PCAs (n = 31) included abdominal pain alone in four patients (13 %), pancreatitis in three (10 %), peritonitis in one (3 %), and gastric wall cyst in one (3 %). The adverse events were classified as moderately severe in four patients (three with pancreatitis, one with peritonitis). Conclusion: EUS-PCA with ethanol and paclitaxel may possibly eliminate mutant DNA in neoplastic pancreatic cysts. This technique leads to complete or partial image-defined resolution in 75 % of cysts but may lead to rare adverse events.Clinical trial registration: ClinicalTrials.gov (NCT01643460)